Analisis Kualitas Pelayanan Terhadap Tingkat Kepuasan Pasien di Rumah Sakit Muhammadiyah Bandung - Maulidda, Yusti; Puspita Dewi, Lies Anggi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze service quality, measure patient satisfaction, and examine the influence of service quality on patient satisfaction at Muhammadiyah Hospital Bandung. The research method used is quantitative, with data collected through a Google Form questionnaire distributed to 83 respondents. The results show that the overall service quality is categorized as good, with an average score of 3.06 on a 4-point scale. The Responsiveness dimension received the highest score (3.15), while the Tangible dimension had the lowest (3.01). Patient satisfaction was in the satisfied category with an average score of 3.10, where 78.3% of respondents reported being satisfied to very satisfied. Statistical analysis revealed that service quality has a positive and significant effect on patient satisfaction, with a correlation coefficient of 0.648 and a coefficient of determination (R²) of 0.420. The t-test result showed a t-count of 7.652 > t-table 1.984 (significance value 0.000), confirming that service quality significantly affects patient satisfaction. Therefore, improving service quality can significantly enhance patient satisfaction at Muhammadiyah Hospital Bandung.